ANALYSIS OF THE CAUSES OF RELAPAROTOMY FOLLOWING SURGERY FOR GENERALIZED PURULENT PERITONITIS - Rakhmatullayev Jurabek Dilmurot o'g'li; Safoyev Baqodir Barnoyevich; Boltayev Temur Shavkatovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Relevance of the Topic. Peritonitis is one of the most severe and frequent complications of acute abdominal diseases, occurring in up to 80% of patients with pathologies of the abdominal organs. The mortality rate for diffuse purulent peritonitis is 15-55%, while for generalized peritonitis it is 65-80%. This persistently high mortality rate demonstrates the continued relevance of this disease in the 21st century.